Dampak Sosial Ekonomi Program Kota Tanpa Kumuh (KOTAKU) di Kabupaten Pandeglang - Sanjaya, Natta; Widyantoro, Sigid; Nurika Akhni, Ghaziah; Kurnia Dewi, Winda; Qurrota A'yun, Soffie (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
Pandeglang Regency has 201,16 hectares of slum areas spread across 37 locations in 13 sub-districts. The Kota Tanpa Kumuh (KOTAKU) program in Pandeglang Regency still has several problems in its implementation, namely the lack of active community involvement, the location of the program target is not evenly distributed, the program is not oriented to the poor community at large, the mismatch of the program rolled out with the conditions needed by the community, the utilization and maintenance of program results are not carried out optimally. The purpose of this research is to find out what are the social and economic impacts of the KOTAKU program in Pandeglang Regency. The research method used is a qualitative research method with a descriptive approach. The results showed that the social impact of the KOTAKU program is to increase active participation and awareness in the community to work together to implement development, improve the quality of life and health of the community, and a sense of ownership of the infrastructure built together. The economic impact of the KOTAKU program is an increase in community welfare and income, job creation, increased work and economic mobility of residents, and efficiency of household living needs.